The era of scarcity: population and global challenges - Fanjul, Gonzalo (Razón y fe, 2018)
In just twelve years the world population has grown from six to seven billion inhabitants. A terrifying figure, to which experts and governments do not know very well how to react. To the already serious food scarcity problem due to the demand by many human beings, Malthusian thesis, today there are two other disadvantages: energy and international migration. An explosive cocktail that can lead many governments to "divine fatalism", in which the humans are not fully respected.